In vitro Screening of Sunflower Associated Endophytic Bacteria With Plant Growth-Promoting Traits - Adeleke, Bartholomew Saanu; Ayangbenro, Ayansina Segun; Babalola, Olubukola Oluranti (Frontiers in Sustainable Food Systems, 2022)
Harnessing endophytic microbes as bioinoculants promises to solve agricultural problems and improve crop yield. Out of fifty endophytic bacteria of sunflowers, 20 were selected based on plant growth-promoting. These plant growth-promoting bacteria were identified as Bacillus, Pseudomonas, and Stenotrophomonas. The qualitative screening showed bacterial ability to produce hydrogen cyanide, ammonia, siderophore, indole-3-acetic acid (IAA), exopolysaccharide, and solubilize phosphate. The high quantity of siderophore produced by B. cereus T4S was 87.73%. No significant difference was observed in the Bacillus sp. CAL14 (33.83%), S. indicatrix BOVIS40 (32.81%), S. maltophilia JVB5 (32.20%), S. maltophilia PK60 (33.48%), B. subtilis VS52 (33.43%), and P. saponiphilia J4R (33.24%), exhibiting high phosphate-solubilizing potential. S. indicatrix BOVIS40, B. thuringiensis SFL02, B. cereus SFR35, B. cereus BLBS20, and B. albus TSN29 showed high potential for the screened enzymes. Varied IAA production was recorded under optimized conditions. The medium amended with yeast extract yielded high IAA production of 46.43 µg/ml by S. indicatrix BOVIS40. Optimum IAA production of 23.36 µg/ml and 20.72 µg/ml at 5% sucrose and 3% glucose by S. maltophilia JVB5 and B. cereus T4S were recorded. At pH 7, maximum IAA production of 25.36 µg/ml was obtained by S. indicatrix BOVIS40. All the isolates exhibited high IAA production at temperatures 25oC, 30oC, and 37oC. The in vitro seed inoculation enhanced sunflower seedlings compared to the control. Therefore, exploration of copious endophytic bacteria as bioinoculants can best be promising to boost sunflower cultivation.